2007
DOI: 10.1016/j.febslet.2007.01.093
|View full text |Cite
|
Sign up to set email alerts
|

Virus membrane fusion

Abstract: Membrane fusion of enveloped viruses with cellular membranes is mediated by viral glycoproteins (GP). Interaction of GP with cellular receptors alone or coupled to exposure to the acidic environment of endosomes induces extensive conformational changes in the fusion protein which pull two membranes into close enough proximity to trigger bilayer fusion. The refolding process provides the energy for fusion and repositions both membrane anchors, the transmembrane and the fusion peptide regions, at the same end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
207
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(213 citation statements)
references
References 50 publications
1
207
0
1
Order By: Relevance
“…The fusogenic ability of VSV G has been of significant interest, because, unlike the proposed "spring-loaded" and essentially irreversible metastable state for the pre-fusion state of other fusion proteins such as influenza HA strain X-31 (10), VSV G is apparently fully reversible for fusion activation; it exists in a dynamic equilibrium between the pre-fusion and post-fusion states (11). In addition, whereas most viral fusion proteins can be categorized into an obvious structural group, either class I or class II (12,13), the distinct structural features of VSV G (14,15) have resulted in it being considered a novel "class III" fusion protein (16).…”
mentioning
confidence: 99%
“…The fusogenic ability of VSV G has been of significant interest, because, unlike the proposed "spring-loaded" and essentially irreversible metastable state for the pre-fusion state of other fusion proteins such as influenza HA strain X-31 (10), VSV G is apparently fully reversible for fusion activation; it exists in a dynamic equilibrium between the pre-fusion and post-fusion states (11). In addition, whereas most viral fusion proteins can be categorized into an obvious structural group, either class I or class II (12,13), the distinct structural features of VSV G (14,15) have resulted in it being considered a novel "class III" fusion protein (16).…”
mentioning
confidence: 99%
“…Rather unexpectedly, we demonstrate that efficient paramyxovirus F-protein-mediated viral entry can proceed independent of complete 6HB assembly. It was suggested that, after activation of paramyxovirus Fprotein refolding and insertion of the fusion peptide into the target membrane, hairpin formation and the assembly of the 6HB fusion core structure pull the viral and target membranes together (1,41,42). This model applies the energy released through formation of the thermodynamically stable fusion core directly to local membrane bending, and the fusion peptides and transmembrane domains function merely as anchor points that are required to transmit elastic stress into the membranes.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that in eukaryotes, this process is mediated by viral proteins, which help the virus introduce its genetic material into the host cells [14,15]. The first step in a cell infection consists in the binding of certain proteins with specific receptors on the membrane, which can be either proteins, lipids or carbohydrates.…”
Section: Introductionmentioning
confidence: 99%